2019
DOI: 10.1002/edm2.58
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in type 2 diabetic subjects randomized to liraglutide or glimepiride treatment, both in combination with metformin: A randomized, open, parallel‐group study

Abstract: Summary Aims Reduced heart rate variability (HRV) and increased heart rate (HR) are associated with cardiovascular (CV) mortality. In the Liraglutide Effect and Action in Diabetes outcome trial, it was demonstrated a lower rate of CV events in type 2 diabetes (T2D) patients treated with liraglutide compared to placebo. We aimed to investigate the effects of liraglutide compared with glimepiride treatment in T2D patients on the CV risk parameters HR and HRV. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Sammito et al reported HF values between 16.41 and 31.92 power% for the age group of 20-60 years [11]. A recent study evaluating the effects of combination treatment of metformin with either liraglutide or glimepiride reported similar results with no significant changes in RMSSD, LF, and HF and LF/HF ratio with the oral hypoglycemic drugs [12].…”
Section: Discussionmentioning
confidence: 94%
“…Sammito et al reported HF values between 16.41 and 31.92 power% for the age group of 20-60 years [11]. A recent study evaluating the effects of combination treatment of metformin with either liraglutide or glimepiride reported similar results with no significant changes in RMSSD, LF, and HF and LF/HF ratio with the oral hypoglycemic drugs [12].…”
Section: Discussionmentioning
confidence: 94%
“…Among these, ten studies were excluded (reasons reported in Fig. 1) and six studies were enrolled [25][26][27][28][29][30] in the final analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is characterized by a "shift" of the sympatho-vagal balance with reduction of the LF component and no change in parasympathetic tone (HF) [26]. In contrast, Nystrom et al [30] demonstrated the absence of changes in sympathetic or parasympathetic activity evaluated by HRV in 62 T2DM individuals receiving 1.8 mg liraglutide once daily in comparison with 4 mg glimepiride once daily. Similarly, in the context of T1DM, changes neither in the HRV domains, nor in cardiac vagal tone and cardiac sensitivity to the baroreflex were observed in 19 patients treated with liraglutide for 26 weeks [25].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, ten studies were excluded (reasons reported in Fig. 1) and six studies were enrolled [25][26][27][28][29][30] in the nal analysis ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is characterized by a "shift" of the sympatho-vagal balance with reduction of the LF component and no change in parasympathetic tone (HF) 26 . In contrast, Nystrom et al demonstrated the absence of changes in sympathetic or parasympathetic activity evaluated by HRV in 62 T2DM individuals receiving 1.8 mg liraglutide once daily in comparison with 4 mg glimepiride once daily 30 . Similarly, in the context of type 1 DM (T1DM), changes neither in the HRV domains, nor in cardiac vagal tone and cardiac sensitivity to the barore ex were observed in 19 patients treated with liraglutide for 26 weeks 25 .…”
Section: Glp-1rmentioning
confidence: 89%